Employee Perceptions of the Brand Salience and Differentiation for a State Forestry Organization - Quisto Settle; Lauri M. Baker; Tracy Irani (Journal of Applied Communications, 2014)
A survey was conducted of employees of the Florida Forest Service (FFS) to determine their perceptions related to the brand ’s differentiation and salience as well as what they believed public perceptions were. Employees’ perceptions are important to the FFS brand. As a service-oriented organization, FFS employees will largely affect public perceptions of the organization and its activities. Employees believed all FFS activities were important but that wildfire-related activities and functions were more salient and more important for differentiating the FFS brand from similar organizations. The employees believed the public was not well informed of FFS’s functions, with the exception of wildfire functions. Employees also believed the public perceived wildfire activities were more important for brand differentiation that FFS’s other activities. Because FFS is a public organization with a variety of functions and activities, it risks its credibility if it is not able to represent the full scope of its activities and functions to the public. It was recommended to make salience and differentiation a priority for the FFS brand. The FFS brand needs to increase the public’s exposure to the FFS brand and represent the full scope of its activities and functions to ensure credible representation of the brand. For research, it was recommended to study tactics for affecting employee perceptions of the organization’s activities and employees’ perceptions of public opinion.
Keywords: branding; brand differentiation; brand salience; public organization; employees